2012
DOI: 10.1074/jbc.m111.333146
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional Inhibition of Luciferase Reporter Assays by the Nod-like Receptor Proteins NLRX1 and NLRC3

Abstract: Background: A number of Nod-like receptors (NLRs) have been shown to inhibit signal transduction pathways using luciferase reporter assays (LRAs). Results: Overexpression of NLRX1 and NLRC3 results in nonspecific post-transcriptional inhibition of LRAs. Conclusion: LRAs are not a reliable technique to assess the inhibitory function of NLRs. Significance: The inhibitory role of NLRs on specific signal transduction pathways needs to be reevaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 36 publications
1
24
3
Order By: Relevance
“…Previous reports identified a role for NLRX1 as a negative regulator of antiviral signaling through a direct interaction with the adaptor molecule mitochondrial antiviral signaling protein on the cytosolic side of the mitochondrial outer membrane (2). However, studies from two other groups, including ours, did not confirm these findings (35). Instead, we demonstrated that NLRX1 was targeted to the mitochondrial matrix through a functional N-terminal addressing sequence (6), a result that was independently confirmed by other studies (7, 8).…”
Section: Introductioncontrasting
confidence: 82%
“…Previous reports identified a role for NLRX1 as a negative regulator of antiviral signaling through a direct interaction with the adaptor molecule mitochondrial antiviral signaling protein on the cytosolic side of the mitochondrial outer membrane (2). However, studies from two other groups, including ours, did not confirm these findings (35). Instead, we demonstrated that NLRX1 was targeted to the mitochondrial matrix through a functional N-terminal addressing sequence (6), a result that was independently confirmed by other studies (7, 8).…”
Section: Introductioncontrasting
confidence: 82%
“…However, the exact function of NLRX1 in Mw is not well understood. Some studies suggest that it negatively regulates MAVS-dependent antiviral responses [29,87] as well as LPS-induced, Toll-like receptor (TLR)-dependent NF-kB activation [88], whereas other studies found no effect [89] or attributed its inhibitory effects to an artifact [90]. Interestingly, it was recently shown that NLRX1 regulates mitochondrialmediated apoptosis and consequently type I IFN in IAV-infected AMw by interacting with the pro-apoptotic viral protein PB1-F2 [91].…”
Section: Reviewmentioning
confidence: 99%
“…Conflicting results do exist, however, as subsequent studies in two independently derived NLRX1 −/− MEFs found no potentiation of IFN induction or IRF3 phosphorylation in response to poly(I:C) stimulation or Sendai virus (SeV) infection compared to wild-type MEFs and no change in the serum level of IFNβ in NLRX1 −/− mice compared to wild-type mice upon injection with poly(I:C) [38,39]. Another study reported NLRX1-mediated inhibition of RLR signaling to be an artifact of inhibition of luciferase activity, which is quite relevant since many of the previous studies used luciferase-based assays to measure RLR signaling [40]. Like LGP2 inhibition of MAVS activity, NLRX1 inhibition of MAVS activity has yielded conflicting results.…”
Section: Mavs Regulation At the Mitochondrial Membranementioning
confidence: 99%